Aspirin modulates inflammatory biomarkers in patients with subcortical silent brain infarcts - Sung, Wonjae; Kim, Young Seo; Lee, Kyu-Yong; Jung, Jae-A; Choi, Hojin; Lee, Young Joo; Koh, Seong-Ho (Frontiers in Aging Neuroscience, 2025)
IntroductionThis study aimed to identify differences in the levels of inflammation-related biomarkers between patients with subcortical silent brain infarcts (SBIs) and healthy controls. We also evaluated the effect of aspirin on the subcortical SBI inflammatory processes.MethodsConsecutive patients diagnosed with subcortical SBIs without a history of acute stroke were included. The demographic and clinical data of the 26 subjects with subcortical SBIs, such as the number and location of subcortical SBIs, were reviewed. Plasma levels of macrophage migration inhibitory factor (MIF), matrix metalloproteinase-9 (MMP-9), and visfatin were measured in patients with subcortical SBIs and ten healthy participants. These biomarkers were rechecked in patients with subcortical SBI 3 months after taking aspirin (100 mg/day).ResultsMIF and MMP-9 levels were significantly higher in patients with subcortical SBIs than in healthy control group (p = 0.031 and p = 0.026, respectively). Although MIF and MMP-9 did not show significant changes after taking aspirin for 3 months, the median plasma level of visfatin was significantly decreased from 1.00 ng/mL (range, 0.86–1.16 ng/mL) to 0.84 ng/mL (range, 0.77–0.91 ng/mL) (p = 0.002) after taking aspirin.DiscussionInflammation could be an essential factor in the pathogenesis of subcortical SBIs, and aspirin affects several inflammation-related biomarkers.